Proposal and operational evaluation of a device for external and internal photodynamic therapy treatments - Enrique Navarrete de Gálvez; Pablo Fonda Pascual; José Aguilera Arjona; José Ramón de Andrés Díaz; María Navarrete de Gálvez; Shiran Perera Mohamed; María Victoria de Gálvez Aranda (Photodiagnosis and Photodynamic Therapy)
Photodynamic therapy (PDT) light sources must match their emission spectrum with the absorption spectrum of the photosensitizer, provide precise treatment definition, deliver adequate irradiance, avoid thermal damage, and minimize treatment duration. Additionally, they should be adaptable to different photosensitizers, easy to manipulate, and cost-effective.Current LED sources are difficult to customize, rigid, and primarily designed for broad-area treatments. For localized treatments, laser technology is commonly employed.We propose a customizable and programmable LED-based device that not only meets these specifications but also addresses the limitations of current LED sources for localized treatments. It allows for the connection of a fiber optic terminal for internal treatments and can be fitted with light-diffusing devices capable of treating lesions externally or penetrating them internally. This device is an enhanced version of a previously developed source that has demonstrated efficacy in several pilot studies of photodynamic therapy.The proposed equipment shows significant potential for both medical and research applications, enabling the configuration of emission spectra on demand and the establishment of tailored treatment protocols based on the type of lesion being treated.